Ruta graveolens Protects Against Isoniazid/Rifampicin-Induced Nephrotoxicity through Modulation of Oxidative Stress and Inflammation - Ayman M Mahmoud; Omnia E Hussein; Mousa O Germoush (Global Journal of Biotechnology and Biomaterial Science - Peertechz Publications, 2016)
Background and Aim Drug-induced nephrotoxicity is a renal dyfunction that arises as a result of exposure to nephrotoxic drugs. Anti-tuberculosis therapy can cause nephrotoxicity and permanent kidney  damage. The  current  study  was  designed  to  evaluate  the  possible  protective  effects  of Ruta graveolens L. leaves extract against isoniazid/rifampicin-induced nephrotoxicity in rats. Methods:The experimental rats received isoniazid and rifampicin at dose level of 50 mg/kg, and 50 or 100 mg/kg/day Ruta graveolens leaves extract orally for 45 days. Results: Isoniazid/ rifampicin administration induced kidney injury evidenced by the histopathological alterations as well as significant (P<0.001) increase in serum creatinine, urea and uric acid. soniazid/rifampicin-intoxicated rats exhibited a significant increase in serum tumor necrosis factor alpha (P<0.001), and renal lipid peroxidation (P<0.01) and nitric oxide (P<0.001) levels. On the other hand, reduced glutathione level, and activity of superoxide dismutase and glutathione peroxidase were  markedly  (P<0.001)  declined  in  kidney  of  isoniazid/rifampicin-induced rats.Concomitant supplementation  with  either  50 or 100  mg/kg  dose  of Ruta  graveolens  leaves  extract  prevented  the isoniazid/rifampicin-induced biochemical and histopathological alterations. Conclusion:The present investigation confers new information on the protective mechanism of Ruta graveolens leaves extract on anti-tuberculosis therapy-induced nephrotoxicity.Ruta graveolens protects  against isoniazid/rifampicin-induced renal injury through attattenuation of inflammation and oxidative stress, and potentiation of the antioxidant defense system.